A Survey of Metaheuristics Approaches for Application in Genomic data - Phogat, Manu; Kumar, Dharmender (International Journal of Computer Sciences and Engineering, 2025)
the present era is the revolutionary time in genomic applications. In recent years, genomes of various species have been sequenced; genes and proteins have been mapped and learned. Structures of genes and proteins have been implied and their behavior is being understood. Over the past two decades, there is a viable interest in to analysis of gene sequence and microarray data with the help of metaheuristics techniques. Therefore this survey intended to give some nature inspired methods to analyze genomic data such as sequence analysis of various genes, microarray analysis and multiple sequence alignment. The survey later on is followed by the types of main nature inspired algorithms both population and single solution based methods. These are followed by their different application in genomic data and their merits to address specific task.